Speech Acts in COVID-19 Infographic Video: (Lakuan Pertuturan dalam Video Infografik COVID-19) (Jurnal Bahasa, 2021)
This study focused on the analysis of Searle's speech acts (1969) in the COVID-19 infographic video by the Ministry of Health Malaysia (KKM). In general, this study was conducted to analyse the speech acts that were used by KKM in their infographic video. The speech acts were identified and analysed based on Searle's Speech Act Theory (1969). This theory highlights five speech acts, namely assertives, expressives, directives, commissives and declaratives. The research method used by the researcher is qualitative method by using content analysis as the research approach. The results showed that there was a total of 129 speech acts that include the five speech acts of Searle (1969). Of these, the directive speech acts were the most dominant and frequently used, totalling 67, followed by assertive speech acts, totalling 51. The third most frequently used speech act was expressive speech acts, totalling 6. Commissive and declarative speech acts were the least frequently used in the COVID-19 infographic video, totalling 4 and 1 respectively. The findings show that directive speech acts were the most dominant because the objective of the infographic video was to convey information on the orders of the Prime Minister and KKM. The use of the Speech Act Theory (Searle, 1969) was seen to be very effective in unravelling the meanings of the communicative intent of the speaker. Therefore, the effectiveness of the information conveyed can have a positive impact on the country and its society.